Association mapping of North American spring wheat breeding germplasm reveals loci conferring resistance to Ug99 and other African stem rust races. Issue 1 (December 2015) - Bajgain, P.; Rouse, MN; Bulli, P.; Bhavani, S.; Gordon, T.; Wanyera, R.; Njau, PN; Legesse, W.; Anderson, JA; Pumphrey, MO
Abstract Background The recently identifiedPuccinia graminis f. sp.tritici (Pgt ) race TTKSK (Ug99) poses a severe threat to global wheat production because of its broad virulence on several widely deployed resistance genes. Additional virulences have been detected in the Ug99 group of races, and the spread of this race group has been documented across wheat growing regions in Africa, the Middle East (Yemen), and West Asia (Iran). Other broadly virulentPgt races, such as TRTTF and TKTTF, present further difficulties in maintaining abundant genetic resistance for their effective use in wheat breeding against this destructive fungal disease of wheat. In an effort to identify loci conferring resistance to these races, a genome-wide association study was carried out on a panel of 250 spring wheat breeding lines from the International Maize and Wheat Improvement Center (CIMMYT), six wheat breeding programs in the United States and three wheat breeding programs in Canada. Results The lines included in this study were grouped into two major clusters, based on the results of principal component analysis using 23, 976 SNP markers. Upon screening for adult plant resistance (APR) to Ug99 during 2013 and 2014 in artificial stem rust screening nurseries at Njoro, Kenya and at Debre Zeit, Ethiopia, several wheat lines were found to exhibit APR. The lines were also screened for resistance at the seedling stage against races TTKSK, TRTTF, and TKTTF at USDA-ARS Cereal Disease Laboratory in St. Paul, Minnesota; and only 9 of the 250 lines displayed seedling resistance to all the races. Using a mixed linear model, 27 SNP markers associated with APR against Ug99 were detected, including markers linked with the known APR geneSr2 . Using the same model, 23, 86, and 111 SNP markers associated with seedling resistance against races TTKSK, TRTTF, and TKTTF were identified, respectively. These included markers linked to the genesSr8a andSr11 providing seedling resistance to races TRTTF and TKTTF, respectively. We also identified putatively novelSr resistance genes on chromosomes 3B, 4D, 5A, 5B, 6A, 7A, and 7B. Conclusion Our results demonstrate that the North American wheat breeding lines have several resistance loci that provide APR and seedling resistance to highly virulentPgt races. Using the resistant lines and the SNP markers identified in this study, marker-assisted resistance breeding can assist in development of varieties with elevated levels of resistance to virulent stem rust races including TTKSK.